Engage : college reading - Dole, Ivan G., 4 0 16; Taggart, Leslie; 5 (Australia : Wadsworth, Cengage Learning, 2013)
Taking a holistic approach to developmental reading, Engage : college reading is the third book in a 3-book series, covering reading levels grades 10-12. It guides students through a stepped and incremental approach, activating background or prior knowledge as many of the skills students need to become critical readers are skills they already possess and use on a daily basis. Often using popular media as a springboard, Dole and Taggart show students how the skills used when watching television or movies can easily transfer to their academic reading. In this third book, Engage offers a much greater emphasis on critical thinking, academic reading and reading for careers. Reviewers have lauded the inclusion of varied, interesting readings that will stimulate students' interest in reading and will provide them with background knowledge needed for the most popular college courses.--Publisher description.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Critical thinking.;Reading comprehension.;Study skills; 20; 2